Prevalence of musculoskeletal disorders among the house wives following kitchen work - Chovatiya, Nandani K.; Solanki, Mayur (International Journal Of Community Medicine And Public Health, 2022)
Background: Kitchen work related pain is one of the commonest problems now a day in housewives. During the kitchen work females have to work in awkward postures, prolonged working positions, repeated movements, improper working environment and manual handling of objects with different size, shape and weights. This study was aimed to find out the prevalence of musculoskeletal disorders (MSDs) in housewives following kitchen work. Methods: The study examined 85 healthy housewives aged between 20 to 45 years from Ahmedabad. Participants were selected as per selection criteria by simple random sampling. Written informed consent was taken from all the participants and participants were requested to fill up the questionnaires. The questionnaires- Cornell musculoskeletal discomfort questionnaire (CMDQ) and Cornell hand discomfort questionnaire (CHDQ) were used in this study. Participants were not involved in any other type of work. Results: The result of the study showed that there was high prevalence of musculoskeletal pain in lower back (64.61%), neck (61.18%), upper back (56.47%), hand (55.29 %), and wrist (52.38%) areas. Conclusions: The study concluded that high prevalence of musculoskeletal discomfort was found among the housewives following kitchen work with predominant affection of lower back, neck, upper back, hand and wrist areas.